Active microbial ecosystem in glacier basal ice fuelled by iron and silicate comminution‐derived hydrogen. Issue 4 (19th July 2021) - Toubes‐Rodrigo, Mario; Potgieter‐Vermaak, Sanja; Sen, Robin; Oddsdóttir, Edda S.; Elliott, David; Cook, Simon
Abstract: The basal zone of glaciers is characterized by physicochemical properties that are distinct from firnified ice due to strong interactions with underlying substrate and bedrock. Basal ice (BI) ecology and the roles that the microbiota play in biogeochemical cycling, weathering, and proglacial soil formation remain poorly described. We report on basal ice geochemistry, bacterial diversity (16S rRNA gene phylogeny), and inferred ecological roles at three temperate Icelandic glaciers. We sampled three physically distinct basal ice facies (stratified, dispersed, and debris bands) and found facies dependent on biological similarities and differences; basal ice character is therefore an important sampling consideration in future studies. Based on a high abundance of silicates and Fe‐containing minerals and, compared to earlier BI literature, total C was detected that could sustain the basal ice ecosystem. It was hypothesized that C‐fixing chemolithotrophic bacteria, especially Fe‐oxidisers and hydrogenotrophs, mutualistically support associated heterotrophic communities. Basal ice‐derived rRNA gene sequences corresponding to genera known to harbor hydrogenotrophic methanogens suggest that silicate comminution‐derived hydrogen can also be utilized for methanogenesis. PICRUSt‐predicted metabolism suggests that methane metabolism and C‐fixation pathways could be highly relevant in BI, indicating the importance of these metabolic routes. The nutrients and microbial communities release from melting basal ice may play an important role in promoting pioneering communities establishment and soil development in deglaciating forelands. Abstract : The subglacial ecosystem is globally significant because glaciers and ice sheets cover 10% of the Earth's land surface, yet it remains poorly understood. This study provides a detailed characterization of the geochemistry and bacterial community inhabiting the subglacial basal ice layer of three Icelandic glaciers. Our data show that a thriving chemolithotroph‐powered community exists within basal ice, fuelled by the oxidation of hydrogen and iron.